Comparative Analysis of Temperature Distributions in a Convective-Radiative Porous Fin using Homotopy Perturbation and Differential Transformation and Methods - Gbeminiyi Musibau Sobamowo; Suraju Aremu Oladosu; Rafiu Olalekan Kuku; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
In this work, a comparative study of two approximate analytical methods for the thermal behaviour of convective-radiative porous fin subjected to the magnetic field using homotopy perturbation and differential transform methods is presented. Also, parametric studies of the effects of thermal-geometric and thermo-physical fin parameters are investigated. From the study, it is found that an increase in a magnetic field, porosity, convective, radiative, and parameters increase the rate of heat transfer from the fin and consequently improves the efficiency of the fin. There are good agreements between the results of the homotopy perturbation and differential transform method with the results of the numerical method. Also, the results of the two approximate analytical methods agree very well with each other. It is hoped that the present work will serve as the basis of verifications of the other works on the nonlinear thermal analysis of the extended surface.